(untitled) (Journal of Advanced Veterinary and Animal Research, 2024)
CRISPR-associated proteins and clustered regularly interspaced short palindromic repeats (CRISPR-Cas) technology has emerged as a groundbreaking advancement in animal and poultry nutrition to improve feed conversion efficiency, enhance disease resistance, and improve the nutritional quality of animal products. Despite significant advancements, there is a research gap in the systematic understanding and comprehensive use of the CRISPR-Cas method in animal and poultry nutrition. The purpose of this study is to elucidate the latest advancements in animal and poultry nutrition through CRISPR-Cas genome editing technology, focusing on gene manipulation in metabolism, immunity, and growth. Following preferred reporting items in meta-analysis and systematic reviews guidelines, we conducted a systematic search using several databases, including Scopus, PubMed, and Web of Science, until May 2024, and finally, we included a total of 108 articles in this study. This article explores the use of the CRISPR-Cas system in the advancement of feed additives like probiotics and enzymes, which could reduce the use of antibiotics in animal production. Furthermore, the article discusses ethical and regulatory issues related to gene editing in animal and poultry nutrition, including concerns about animal welfare, food safety, and environmental impacts. Overall, the CRISPR-Cas system holds substantial promise to overcome the challenges in modern animal agriculture. By enriching the nutritional quality of animal products, increasing disease resistance, and improving feed efficiency, it offers sustainable and cost-effective solutions that can revolutionize animal and poultry nutrition. Adv. Vet. Anim. Res., 11(2): 483-493, June 2024 http://doi.org/10.5455/javar.2024.k798